A qualitative investigation of the health economic impacts of bariatric surgery for obesity and implications for improved practice in health economics. (1st June 2018) - Campbell, Julie A.; Ezzy, Douglas; Neil, Amanda; Hensher, Martin; Venn, Alison; Sharman, Melanie J.; Palmer, Andrew J.
Summary: Obesity is an economic problem. Bariatric surgery is cost‐effective for severe and resistant obesity. Most economic evaluations of bariatric surgery use administrative data and narrowly defined direct medical costs in their quantitative analyses. Demand far outstrips supply for bariatric surgery. Further allocation of health care resources to bariatric surgery (particularly public) could be stimulated by new health economic evidence that supports the provision of bariatric surgery. We postulated that qualitative research methods would elicit important health economic dimensions of bariatric surgery that would typically be omitted from the current economic evaluation framework, nor be reported and therefore not considered by policymakers with sufficient priority. We listened to patients: Focus group data were analysed thematically with software assistance. Key themes were identified inductively through a dialogue between the qualitative data and pre‐existing economic theory (perspective, externalities, and emotional capital). We identified the concept of emotional capital where participants described life‐changing desires to be productive and participate in their communities postoperatively. After self‐funding bariatric surgery, some participants experienced financial distress. We recommend a mixed‐methods approach to the economic evaluation of bariatric surgery. This could be operationalised in health economic model conceptualisation and construction, through to the separate reporting of qualitative results to supplement quantitative results.